Operando Spectroscopy in Photocatalysis. Issue 9 (1st August 2018) - Caudillo‐Flores, Uriel; Muñoz‐Batista, Mario J.; Kubacka, Anna; Fernández‐García, Marcos
Abstract: The use of operando spectroscopic tools in heterogeneous photocatalysis has experienced a strong drive in recent years. When using operando tools we must, however, consider carefully the fraction of the system to be probed in an in situ cell, that is, the volume under the simultaneous influence of excitation light and the reactants. This is not an obvious task for certain spectroscopies, particularly for those attempting to characterize the physico‐chemical state of the catalysts. Herein we provide an analysis of this point applied to spectroscopies such as XAS (X‐ray absorption spectroscopy) and complete the analysis of operando tools with those aimed to characterize the surface of the photocatalysts (XPS; X‐ray photoelectron spectroscopy) as well as those spectroscopies, such as infrared or Raman, focusing on the study of the reactant−catalyst interface. Abstract : Watch and learn : Operando spectroscopy results in photocatalysis are analyzed in terms of the information rendered for the catalysts and reactant−catalyst interfaces. Application of operando spectroscopic techniques to analyze the catalyst active state as well as the photocatalytic mechanism and relevant kinetic steps is discussed.